Face and Gesture 2011 2011
DOI: 10.1109/fg.2011.5771442
|View full text |Cite
|
Sign up to set email alerts
|

Warp that smile on your face: Optimal and smooth deformations for face recognition

Abstract: Abstract-In this work, we present novel warping algorithms for full 2D pixel-grid deformations for face recognition.Due to high variation in face appearance, face recognition is considered a very difficult task, especially if only a single reference image, for example a mug-shot, per face is available.Usually model-based approaches with additional training data are used to cope with several types of variation occurring in facial imaging. Image warping contrarily yields a distance measure which is invariant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…We start by briefly reviewing the problem formulation of 2D warping in correspondence with [5] and [6]. Given a source image X = {x ij } with resolution I ×J and a target image R = {r uv } with resolution U × V , we search for a mapping (i, j) → w ij = (u, v) that assigns each pixel of the source image to a pixel of the target image with minimal energy cost.…”
Section: D Warpingmentioning
confidence: 99%
See 4 more Smart Citations
“…We start by briefly reviewing the problem formulation of 2D warping in correspondence with [5] and [6]. Given a source image X = {x ij } with resolution I ×J and a target image R = {r uv } with resolution U × V , we search for a mapping (i, j) → w ij = (u, v) that assigns each pixel of the source image to a pixel of the target image with minimal energy cost.…”
Section: D Warpingmentioning
confidence: 99%
“…We found that this distinction is not necessary and simply matching both half-images and selecting the lower resulting energy is sufficient for all poses. As in [12] and [6] we use the gallery image as source and the probe image as target.…”
Section: D Warpingmentioning
confidence: 99%
See 3 more Smart Citations